2021
DOI: 10.33687/009.01.3510
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder farmers’ perceptions of agricultural extension in adoption of new technologies in Kakamega County, Kenya

Abstract: This exploratory study assesses factors that harness agricultural technology adoption among smallholder farmers in Kakamega County, Kenya by evaluating the key variables that influence sustainable adoption of agricultural innovations in the area. A survey was randomly administered in June and July 2018 among smallholder farming households in seven sub-counties (N=78) of Kakamega County. A logistic regression model, capturing factors presumed to influence the adoption of agricultural innovations, was estimated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…Furthermore, the results in Table 2 show that the perception towards innovation is significantly and positively associated with early adoption decision. This result is in agreement with the findings of Adesina and Zinnah (1993), Batz et al (1999), Llewellyn and Brown (2020), Zhllima et al (2021) and Nyairo et al (2022).…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, the results in Table 2 show that the perception towards innovation is significantly and positively associated with early adoption decision. This result is in agreement with the findings of Adesina and Zinnah (1993), Batz et al (1999), Llewellyn and Brown (2020), Zhllima et al (2021) and Nyairo et al (2022).…”
Section: Resultssupporting
confidence: 93%
“…Studies like that of Delay et al (2022) further reinforce the necessity of a holistic approach, showing that farms employing a comprehensive set of PA technologies tend to be significantly more efficient. But this comprehensive approach may be too expensive for small-scale farmers (Mwangi et al, 2020; Nyairo et al, 2022). In summary, the trajectory of PA adoption among small-scale farmers is shaped by a confluence of factors: the farmer's digital literacy, the robustness of the underlying infrastructure, and the integration of multiple technologies.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This ease of use could serve as a catalyst for broader PA adoption among local farmers. Similarly, Nyairo et al (2022) conducted a study in Kenya that found a significant link between farmers' familiarity with agricultural technologies and their propensity to adopt such tools. The research found that the more acquainted farmers were with certain practices or tools, the more inclined they were to adopt them, whereas unfamiliar techniques met resistance.…”
Section: Hierarchies Of Influence In Precision Agriculture Adoption A...mentioning
confidence: 99%
“…Regarding economic factors, many studies have shown the critical role of farm size in the decision to adopt new technology (Langyintuo & Mungoma, 2008;Manda et al, 2016;Meshram et al, 2016;Mwangi & Kariuki, 2015;Nyairo, Pfeiffer, & Russell, 2021). Large-scale farmers tend to adopt new technology because they can afford to spend part of their land trying out the new technology (Uaiene, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%